Critique & praxis a critical philosophy of illusions, values, and action - Harcourt, Bernard E. 1963- (Columbia University Press, 2020)
Critical philosophy has always challenged the division between theory and practice. At its best, it aims to turn contemplation into emancipation, seeking to transform society in pursuit of equality, autonomy, and human flourishing. Yet today’s critical theory often seems to engage only in critique. These times of crisis demand more.Bernard E. Harcourt challenges us to move beyond decades of philosophical detours and to harness critical thought to the need for action. In a time of increasing awareness of economic and social inequality, Harcourt calls on us to make society more equal and just. Only critical theory can guide us toward a more self-reflexive pursuit of justice. Charting a vision for political action and social transformation, Harcourt argues that instead of posing the question, "What is to be done?" we must now turn it back onto ourselves and ask, and answer, "What more am I to do?"Critique and Praxis advocates for a new path forward that constantly challenges each and every one of us to ask what more we can do to realize a society based on equality and justice. Joining his decades of activism, social-justice litigation, and political engagement with his years of critical theory and philosophical work, Harcourt has written a magnum opus
Keywords: PHILOSOPHY / Movements / Critical Theory; Critical theory; Political participation; Political science -- Philosophy; Social action; Kritische Theorie; Gerechtigkeit